Low-hydrogen permeation PEM electrolyzed water membrane electrode and preparation method thereof
By introducing a perfluorosulfonic acid resin insulating layer into the low-permeable hydrogen PEM electrolytic membrane electrode to isolate the high potential environment, the problem of catalysts being easily corroded and shedded is solved, and the stability and hydrogen removal effect of the membrane electrode are improved.
Patent Information
- Application Number
- CN202411775474.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-05
- Publication Date
- 2025-01-10
AI Technical Summary
The hydrogen removal layer of the existing low-permeable hydrogen PEM electrolytic water membrane electrode is directly connected to the anode catalytic layer, resulting in the catalyst being susceptible to oxidation corrosion, poor stability, and the oxygen evolution catalyst is prone to falling off, affecting the structural stability and durability of the membrane electrode.
A perfluorosulfonic acid resin insulating layer is introduced between the hydrogen-elimination layer and the anode catalytic layer. The high potential environment is isolated by making the insulating layer slightly larger than the hydrogen-elimination layer, improving the stability of the catalyst, and transfer technology The structures of each layer are tightly stacked.
It effectively improves the structural stability and durability of the membrane electrode, avoids oxidative inactivation of the catalyst, and ensures the stability and safety of the hydrogen removal effect.
Smart Images

Figure CN119287410A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of fuel cells, and in particular to a low-hydrogen permeability PEM water electrolysis membrane electrode and a preparation method thereof. Background Art
[0002] Proton exchange membrane (PEM) water electrolysis is considered to be one of the preferred ways to produce green hydrogen, with advantages such as high current density, high-purity hydrogen output and fast response. The membrane electrode is a key component of the PEM electrolyzer. Its structure includes the anode catalyst layer, the cathode catalyst layer and the proton exchange membrane, which directly affects the energy consumption and life of the electrolyzer. During operation, oxygen evolution occurs at the anode and hydrogen is produced at the cathode.
[0003] The performance of membrane electrode is affected by three types of voltage losses: activation polarization, ohmic polarization, and mass transfer polarization, among which ohmic polarization voltage loss is dominant. In order to reduce ohmic polarization loss, the internal resistance is usually reduced by thinning the proton exchange membrane. However, the thin film leads to a decrease in gas barrier properties, especially under high pressure, hydrogen can easily penetrate from the cathode to the anode, mix with oxygen, and pose a safety risk.
[0004] At present, the main methods for removing hydrogen are: adding a hydrogen removal layer in the membrane electrode, coating a hydrogen removal catalyst on the anode side of the electrolyzer, and installing a gas reforming device at the oxygen outlet. Among them, the membrane electrode layer has the best hydrogen removal effect and has high safety and economy. However, the hydrogen removal layer of this method is directly connected to the anode catalyst layer. Due to the high working potential, the catalyst is susceptible to oxidative corrosion and has poor stability. In addition, the catalyst layer is not tightly bonded, and the oxygen evolution catalyst is easy to fall off. Summary of the invention
[0005] Based on this, it is necessary to provide a low hydrogen permeability PEM water electrolysis membrane electrode with good stability and a preparation method thereof.
[0006] To achieve the above object, the present invention provides a technical solution: A low hydrogen permeability PEM water electrolysis membrane electrode comprises, from top to bottom, an anode catalyst layer, an insulating layer, a hydrogen removal layer, a proton exchange membrane and a cathode catalyst layer, wherein the raw material for preparing the insulating layer comprises perfluorosulfonic acid resin.
[0007] More specifically, the insulating layer is located between the anode catalyst layer and the hydrogen removal layer. From a structural point of view, the insulating layer is slightly larger than the hydrogen removal layer and can completely cover it, isolating it from the high potential environment and improving the stability of hydrogen removal. The hydrogen removal catalytic layer is uniform and dense, and can effectively intercept hydrogen permeating from the proton exchange membrane; Compared with the direct connection between the hydrogen removal layer and the anode catalyst layer, the insulating layer located in the middle can make the connection between the two closer, the catalyst is not easy to fall off, and the structural stability and durability of the membrane electrode are improved.
[0008] Furthermore, the method for preparing the insulating layer comprises the steps of: Dispersing perfluorosulfonic acid resin in an alcohol aqueous solution to obtain an insulating layer slurry; The insulating layer slurry is coated on the surface of the base film using a coating machine, and then heated and dried to obtain the insulating layer.
[0009] Furthermore, the bottom plate temperature of the coating machine is 25°C ~ 30°C, the coating wet film thickness is 50μm ~ 120μm, the coating rod line speed is 0.1 m / min ~ 0.5m / min, the heating and drying time is 1 min ~ 15min, and the insulation layer thickness is 5μm ~ 15μm.
[0010] Furthermore, the alcohol includes at least one of methanol, ethanol, n-propanol, isopropanol, ethylene glycol, n-butanol, isobutanol and sec-butanol.
[0011] Furthermore, the steps of preparing the hydrogen removal layer include: The hydrogen removal layer slurry is coated on the surface of the base film, heated and dried to obtain the hydrogen removal layer.
[0012] Furthermore, the coating machine bottom plate temperature is 25~60°C, the coating wet film thickness is 50~120μm, the coating rod line speed is 0.1~0.5m / min, the drying time is 1~15min, the thickness of the dehydrogenation layer is 5~15μm, and the dehydrogenation layer slurry contains a platinum-palladium catalyst.
[0013] Furthermore, the platinum loading is 0.05~0.5 mg / cm 2 .
[0014] The present invention also provides a method for preparing a low hydrogen permeability PEM water electrolysis membrane electrode, comprising the steps of: The anode catalyst layer, insulating layer, hydrogen removal layer, proton exchange membrane and cathode catalyst layer are stacked together in sequence by transfer printing to obtain a low permeability PEM water electrolysis membrane electrode. The transfer temperature is 80℃~180℃, the pressure is 2MPa~5MPa, and the transfer time is 2min~10min.
[0015] Further, the transfer includes a first transfer, a second transfer and a third transfer, and the specific steps are as follows: Placing the hydrogen removal layer and the proton exchange membrane in a transfer machine, and performing a first transfer printing to obtain a first transfer membrane; Placing the insulating layer and the first transfer film in a transfer machine for transfer printing, and performing a second transfer printing to obtain a second transfer film; The anode catalyst layer, the second transfer membrane and the cathode catalyst layer are placed in a transfer machine for transfer in sequence. After the third transfer, a low-permeability hydrogen PEM water electrolysis membrane electrode is obtained.
[0016] The specific preparation steps of low hydrogen permeability PEM water electrolysis membrane electrode are as follows: S100, preparation of anode catalyst layer An aqueous solution of alcohol is added to a perfluorosulfonic acid (PFSA) dispersion, the PFSA dispersion is preliminarily dispersed by an ultrasonic cell disruptor, and then an oxygen evolution catalyst is added, and the dispersion is transferred to a ball mill filled with ball milling beads and sealed, and dispersed again by a ball mill to obtain an anode catalyst slurry; wherein the ball mill is installed in the ball mill to complete rotation and ball milling.
[0017] More specifically, the oxygen evolution catalyst includes at least one of iridium black, iridium oxide, iridium-based supported catalyst and iridium-based alloy catalyst, the solid content of the anode catalyst slurry is 10-30%, the alcohol content is 25%-75%, the ultrasonic power of the ultrasonic cell disruptor is 100-1000W, the ball ratio of the ball mill is (2:1)-(1:4), the rotation speed is 50 rpm-1000rpm, the temperature is -5°C-60°C, and the time is 4 h-72h.
[0018] The anode catalyst slurry is evenly coated on the surface of the base membrane using a desktop coater, and then heated and dried to obtain the anode catalyst layer.
[0019] More specifically, the bottom plate temperature of the coating machine is 25-60°C, the coating wet film thickness is 50 μm-120 μm, the coating rod line speed is 0.1 m / min-0.5 m / min, the drying time of heating and drying is 1 min-15 min, the thickness of the anode catalyst layer is 5 μm-15 μm, and the iridium loading in the anode catalyst layer is 0.3-1.5 mg / cm 2 ~1.5mg / cm 2 .
[0020] S200, Preparation of cathode catalyst layer An alcohol aqueous solution is added to the PFSA dispersion, the PFSA is preliminarily dispersed by an ultrasonic cell disruptor, and then a hydrogen evolution catalyst is added, and the mixture is transferred to a ball mill jar filled with ball mill beads and sealed, and dispersed again by a ball mill to obtain a cathode catalyst slurry; More specifically, the hydrogen evolution catalyst includes at least one of platinum black, platinum carbon, a platinum-based supported catalyst and a platinum-based alloy catalyst, the solid content of the cathode catalyst slurry is 7% to 13%, the alcohol content is 25% to 75%, the ultrasonic power of the ultrasonic cell disruptor is 100 W to 1000 W, the material-ball ratio in the ball mill is 2:1 to 1:4, the rotation speed is 50 rpm to 1000 rpm, the temperature is -5°C to 60°C, and the time is 4 h to 72 h.
[0021] The cathode catalyst slurry is evenly coated on the surface of the base membrane using a desktop coater, and then heated and dried to obtain a cathode catalyst layer.
[0022] More specifically, the bottom plate temperature of the coating machine is 25°C to 60°C, the coating wet film thickness is 50μm to 120μm, the coating rod line speed is 0.1 m / min to 0.5m / min, the drying time is 1 min to 15min, the cathode catalyst layer thickness is 5μm to 15μm, and the platinum loading in the cathode catalyst layer is 0.1 mg / cm 2 ~0.4 mg / cm 2 .
[0023] S300, preparation of hydrogen removal layer Alcohol and deionized water were added to the PFSA dispersion, and the PFSA was preliminarily dispersed by an ultrasonic cell disruptor. Then, a dehydrogenation catalyst was added, and the mixture was transferred to a ball mill filled with ball mill beads and sealed. The mixture was dispersed again by a ball mill to obtain a dehydrogenation layer catalyst slurry.
[0024] More specifically, the solid content of the catalyst slurry of the dehydrogenation layer is 10% to 30%, the alcohol content is 25% to 75%, the ultrasonic power of the ultrasonic cell disruptor is 100 W to 1000 W, the material-ball ratio of the ball mill is (2:1) to (1:4), the rotation speed is 50 rpm to 1000 rpm, the temperature is -5°C to 60°C, and the time is 4 h to 72 h; The dehydrogenation layer catalyst slurry is evenly coated on the surface of the base film using a desktop coater, and heated and dried to obtain the dehydrogenation layer.
[0025] More specifically, the dehydrogenation catalyst includes a platinum-palladium catalyst, such as at least one of platinum black, palladium black, platinum carbon and palladium carbon, the bottom plate temperature of the coating machine is 25° C. to 60° C., the coating wet film thickness is 50 μm to 120 μm, the coating rod line speed is 0.1 m / min to 0.5 m / min, the drying time of the heating drying is 1 min to 15 min, the thickness of the dehydrogenation layer is 5 μm to 15 μm, and the platinum or palladium loading in the dehydrogenation layer is 0.05 mg / cm 2 ~0.5 mg / cm 2 .
[0026] S400, Preparation of insulation layer Adding alcohol and deionized water to the PFSA dispersion, dispersing the PFSA by an ultrasonic cell disruptor with an ultrasonic power of 100-1000 W, to obtain an insulating layer slurry; The insulating layer slurry is evenly coated on the surface of the base film using a desktop coater, and heated and dried to obtain an insulating layer.
[0027] More specifically, the coater bottom plate temperature is 25-30°C, the coating wet film thickness is 50μm-120μm, the coating rod line speed is 0.1 m / min-0.5m / min, the drying time of heating drying is 1 min-15min, and the thickness of the insulating layer is 5μm-15μm.
[0028] S500, Preparation of low hydrogen permeability PEM water electrolysis membrane electrode The anode catalyst layer, insulating layer, hydrogen removal layer, proton exchange membrane and cathode catalyst layer are cut into appropriate sizes and stacked together, wherein the cathode and anode catalyst layers are the same size, the hydrogen removal layer is slightly larger than the anode catalyst layer, and the insulating layer is slightly larger than the hydrogen removal layer.
[0029] Through a transfer machine, under certain temperature and pressure conditions, the hydrogen removal layer, insulation layer, anode and cathode catalyst layers are divided into three times and gradually transferred to both sides of the proton exchange membrane.
[0030] More specifically, the proton exchange membrane is a homogeneous membrane or an enhanced membrane. Specifically, the homogeneous membrane includes at least one of Chemours' N115 and N117, and the enhanced membrane includes at least one of Hydrogen Energy's BriPEM-801, Fumatech's FS-990-PK, and Gore's M275.80. The transfer temperature is 80~180°C, the pressure is 2~5MPa, and the time is 2~10min.
[0031] The PFSA dispersion used in the above steps can be Nafion D520 and D2020 from Chemours in the United States, or D72-25BS, D79-25BS, D87-25BS and D98-25BS from Solvay in Belgium, or IC154 and IC100 from AGC in Japan, or DHx120, DHx220 and DHx320 from Dongyue Future Hydrogen Energy in Shandong Province, PFSA dispersions of different branch lengths produced by different manufacturers, the alcohol is at least one of methanol, ethanol, n-propanol, isopropanol, ethylene glycol, n-butanol, isobutanol and sec-butanol, the ball milling beads are at least one of alumina balls, zirconia balls and agate balls, and the base film is at least one of PI, PTFE, PPS and PET.
[0032] Beneficial effects of the present invention: The present invention adds an insulating layer between the hydrogen removal layer and the anode catalyst layer of the traditional hydrogen removal membrane electrode. On the one hand, the insulating layer can efficiently transfer protons without affecting the electrolysis performance of the membrane electrode; on the other hand, the insulating layer cannot conduct electrons, thereby isolating the hydrogen removal layer from the high-potential working environment, avoiding oxidation and deactivation of the hydrogen removal catalyst, and ensuring the stability of hydrogen removal of the membrane electrode. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Figure 1It is a schematic diagram of the structure of a low hydrogen permeability PEM water electrolysis membrane electrode; Figure 2 This is a cross-sectional electron microscope image of the anode side of the low hydrogen permeability PEM water electrolysis membrane electrode; Figure 3 This is the elemental analysis diagram of the anode side cross section of the low hydrogen permeability PEM water electrolysis membrane electrode; Figure 4 The graphs are for the stability of hydrogen content in oxygen for the examples and comparative examples.
[0034] Among them, 1. anode catalyst layer; 2. insulation layer; 3. hydrogen removal layer; 4. proton exchange membrane; 5. cathode catalyst layer. DETAILED DESCRIPTION
[0035] In order to better illustrate the purpose, technical solutions and advantages of the present invention, the present invention will be further described below in conjunction with specific embodiments.
[0036] In the examples, the test methods used are conventional methods unless otherwise specified, and the materials, reagents, etc. used are all commercially available unless otherwise specified.
[0037] 1. Embodiment 1: S100, preparing anode catalyst layer 1 n-Propanol and deionized water were added to the PFSA dispersion (D79-25BS), and the PFSA was preliminarily dispersed by an ultrasonic cell disruptor. Then, an iridium oxide catalyst (TEC77110, Tanaka Precious Metals) was added, and the mixture was transferred to a ball mill filled with zirconium oxide ball milling beads and sealed. The mixture was dispersed again by a ball mill to obtain an anode catalyst slurry.
[0038] The anode catalyst slurry has a solid content of 25%, an alcohol content of 50%, an ultrasonic power of 300 W, a ball-to-material ratio of the ball mill of 1:1, a rotation speed of 400 rpm, a temperature of 25° C., and a time of 24 h to obtain the anode catalyst slurry; The anode catalyst slurry was evenly coated on the surface of the PTFE membrane using a desktop coater, and then heated and dried to obtain the anode catalyst layer 1.
[0039] The bottom plate temperature of the coating machine is 50°C, the coating wet film thickness is 120 μm, the coating rod line speed is 0.2 m / min, the drying time of heating and drying is 5 min, the thickness of the anode catalyst layer 1 is 8 μm, and the iridium loading in the anode catalyst layer 1 is 1.0 mg / cm 2 .
[0040] S200, preparing cathode catalyst layer 5 n-Propanol and deionized water were added to the PFSA dispersion (D79-25BS), and it was preliminarily dispersed by an ultrasonic cell disruptor. Then, a platinum-carbon catalyst (TEC10F50E-HT, Tanaka Precious Metals) was added, and the mixture was transferred to a ball mill filled with zirconia ball milling beads and sealed. It was dispersed again by a ball mill to obtain a cathode catalyst slurry.
[0041] Among them, the solid content of the cathode catalyst slurry is 10%, the alcohol content is 50%, the ultrasonic power of the ultrasonic cell disruptor is 300W, the material-ball ratio of the ball mill is 1:1, the rotation speed is 200rpm, the temperature is 25°C, and the time is 48h.
[0042] The cathode catalyst slurry is evenly coated on the surface of the PTFE membrane using a desktop coater, and then heated and dried to obtain a cathode catalyst layer 5.
[0043] The bottom plate temperature of the coating machine is 50°C, the coating wet film thickness is 100 μm, the coating rod line speed is 0.2 m / min, the drying time of heating and drying is 5 min, the thickness of the cathode catalyst layer 5 is 10 μm, and the platinum loading in the cathode catalyst layer 5 is 0.3 mg / cm 2 .
[0044] S300, preparing hydrogen removal layer 3 n-Propanol and deionized water were added to the PFSA dispersion (D79-25BS), and it was preliminarily dispersed by an ultrasonic cell disruptor, and then a platinum black catalyst (Heraeus) was added, and it was transferred to a ball mill jar filled with ball mill beads (zirconia balls) and sealed, and dispersed again by a ball mill to obtain a dehydrogenation layer 3 catalyst slurry.
[0045] Among them, the solid content of the dehydrogenation catalyst slurry is 20%, the alcohol content is 50%, the ultrasonic power of the ultrasonic cell disruptor is 300W, the material-ball ratio of the ball mill is 1:1, the rotation speed is 200rpm, the temperature is 25°C, and the time is 24h.
[0046] The cathode catalyst slurry is evenly coated on the surface of the PTFE membrane using a desktop coater, and then heated and dried to obtain a hydrogen removal layer 3.
[0047] The bottom plate temperature of the coating machine is 50°C, the coating wet film thickness is 50 μm, the coating rod line speed is 0.2 m / min, the drying time of heating drying is 5 min, the thickness of the dehydrogenation layer 3 is 2 μm, and the platinum loading in the dehydrogenation layer 3 is 0.3 mg / cm 2 .
[0048] S400, preparing insulating layer 2 Add alcohol and deionized water to the PFSA dispersion (D79-25BS), and disperse the PFSA by using an ultrasonic cell disruptor with an ultrasonic power of 300 W to obtain an insulating layer 2 slurry; The insulating layer 2 slurry is evenly coated on the surface of the PTFE membrane using a desktop coater, and then heated and dried to obtain the insulating layer 2 .
[0049] The bottom plate temperature of the coater is 50° C., the coating wet film thickness is 80 μm, the coating rod line speed is 0.2 m / min, the drying time of heating and drying is 5 min, and the thickness of the insulating layer 2 is 4 μm.
[0050] S500, Preparation of low hydrogen permeability PEM water electrolysis membrane electrode like Figure 1 As shown, the anode catalyst layer 1, the insulating layer 2, the hydrogen removal layer 3, the proton exchange membrane 4 (BriPEM-801, 80 μm thick) and the cathode catalyst layer 5 are cut into appropriate sizes and stacked together, wherein the cathode and anode catalyst layers 1 are the same size, the hydrogen removal layer 3 is slightly larger than the anode catalyst layer 1, and the insulating layer 2 is slightly larger than the hydrogen removal layer 3. Through the transfer machine, at 160°C and 3MPa, the hydrogen removal layer 3, the insulating layer 2, the anode and cathode catalyst layers 5 are divided into three times and gradually transferred to both sides of the proton exchange membrane 4 to obtain a low permeability PEM water electrolysis membrane electrode, and the transfer time is 5 minutes. The specific steps of the step-by-step transfer are as follows: The hydrogen removal layer 3 and the proton exchange membrane 4 are placed in a transfer machine, and after a first transfer, a first transfer membrane is obtained; The insulating layer 2 and the first transfer film are placed in a transfer machine for transfer printing, and after a second transfer printing, a second transfer film is obtained; The anode catalyst layer 1, the second transfer film and the cathode catalyst layer 5 are placed in a transfer machine for transfer in sequence. After the third transfer, a low-permeability hydrogen PEM water electrolysis membrane electrode is obtained.
[0051] Example 2
[0052] The other steps of Example 2 are the same as those of Example 1, except that: The enhanced proton exchange membrane 4 (BriPEM-801) with a thickness of 80 μm in step S500 is replaced with a homogeneous proton exchange membrane 4 (N115) with a thickness of 127 μm.
[0053] Example 3
[0054] The other steps of Example 3 are the same as those of Example 1, except that: The PFSA dispersion (D79-25BS) in steps S100, S200, S300, and S400 was replaced with the PFSA dispersion (D2020).
[0055] Example 4
[0056] The other steps of Example 4 are the same as those of Example 1, except that: The platinum black catalyst in step S300 was replaced with a palladium carbon catalyst (Heraeus).
[0057] Comparative Example 1 The other steps of Comparative Example 1 are the same as those of Example 1, except that: The step S400 of preparing the insulating layer 2 is not included, and the insulating layer 2 is not added in the membrane electrode preparation step S500.
[0058] Comparative Example 2 Comparative Example 2 is an improvement based on Example 2. The difference between Example 2 and Comparative Example 2 is that: The step S400 of preparing the insulating layer 2 is not included, and the insulating layer 2 is not added in the membrane electrode preparation step S500.
[0059] Comparative Example 3 The other steps of Comparative Example 3 are the same as those of Example 1, except that: In the step S300 of preparing the hydrogen removal layer 3, the platinum black catalyst is replaced with a supported platinum catalyst having an insulating carrier tin oxide. The step S400 of preparing the insulating layer 2 is not included, and the insulating layer 2 is not added in the membrane electrode preparation step S500.
[0060] Compared with the existing process, the present invention adds a perfluorosulfonic acid resin (PFSA) insulating layer 2 between the hydrogen removal layer 3 and the anode catalyst layer 1 of the traditional hydrogen removal membrane electrode.
[0061] Figure 2 This is a cross-sectional electron microscope image of the anode side of the low hydrogen permeability PEM water electrolysis membrane electrode prepared in Example 1, as shown Figure 2 As shown, it can be seen that the multilayer structure has different thicknesses, and from left to right are the anode catalyst layer 1, the insulating layer 2, the hydrogen removal layer 3, and the proton exchange membrane 4; Figure 3 This is an elemental analysis diagram of the anode side cross-section of the low hydrogen permeability PEM water electrolysis membrane electrode prepared in Example 1, which includes, from left to right, an anode catalyst layer 1, an insulating layer 2, a hydrogen removal layer 3, and a proton exchange membrane 4. Figure 3 It can be seen that the main element in the anode catalyst layer 1 is iridium, the main element in the hydrogen removal layer 3 is platinum, and the distribution of fluorine elements shows that the main substances in the insulating layer 2 and the proton exchange membrane 4 are perfluorosulfonic acid; The insulating layer 2 isolates the dehydrogenation layer 3 from the high potential anode catalyst layer 1 to prevent the dehydrogenation catalyst from being oxidized and deactivated, thereby ensuring the dehydrogenation stability of the low hydrogen permeability PEM water electrolysis membrane electrode.
[0062] The membrane electrodes prepared in the examples and comparative examples were tested for the in-situ hydrogen content in oxygen.
[0063] Use 25cm 2The single electrolyzer was assembled, the cathode used a direct current channel, the porous transport layer was 0.4mm titanium felt, the anode used a lattice channel, the porous transport layer was 0.4mm platinum-plated titanium felt, and the assembly pressure was 3.5MPa. The test was carried out on the electrolytic water test system, with water supply on one side of the anode, a flow rate of 200ml / min, a temperature of 60℃, normal pressure, and a working current density of 3A / cm 2 , the test results are as follows Figure 4 .
[0064] like Figure 4 As shown, the membrane electrodes provided by Example 1, Example 2, Example 3, and Example 4 have a good hydrogen removal effect, and the hydrogen content in oxygen is lower than that of Comparative Example 1, Comparative Example 2, and Comparative Example 3 without the insulating layer 2.
[0065] At the same time, in the 100h hydrogen removal stability test, the hydrogen content in oxygen in Examples 1 to 3 did not increase, while the hydrogen content in oxygen in Comparative Examples 1, 2 and 3 increased significantly, indicating that the membrane electrode prepared by the present invention has good hydrogen removal stability.
[0066] From the hydrogen content in oxygen of Comparative Example 1 and Comparative Example 1 during the test, it can be seen that the addition of the insulating layer 2 between the hydrogen removal layer 3 and the anode catalyst layer 1 in Example 1 can effectively prevent the hydrogen removal catalyst from being oxidized and improve the hydrogen removal stability. The effect of coating the insulating layer 2 with a perfluorosulfonic acid resin on the hydrogen removal stability in Example 1 is much greater than that of Comparative Example 1 in which only the perfluorosulfonic acid resin is added to the hydrogen removal layer 3.
[0067] From the comparison of the hydrogen content in oxygen in Example 1, Comparative Example 1 and Comparative Example 3 during the test, it can be seen that the difference between Comparative Document 3 and Comparative Document 1 is that when the hydrogen removal layer is prepared in step S300, the supported platinum catalyst of tin oxide on an insulating carrier is used to replace the platinum black catalyst. Although the supported platinum catalyst of tin oxide on an insulating carrier is used as a hydrogen removal layer and has a hydrogen removal effect, that is, the rate of increase of the hydrogen content in oxygen in Comparative Document 3 is much lower than that of Comparative Example 1 using a platinum black catalyst, it is still impossible to achieve the stability of the hydrogen content in oxygen in Example 1, for example, because the insulating carrier catalyst (i.e., the supported platinum catalyst of tin oxide on an insulating carrier in Comparative Example 3) cannot completely shield the high potential environment in which the hydrogen removal catalyst works, and part of the hydrogen removal catalyst is oxidized, resulting in a decrease in the hydrogen removal effect. However, Example 1, in which the hydrogen removal layer 3 is protected by the insulating layer 2, can ensure the long-term stability of the hydrogen content in oxygen, that is, the effect of the insulating layer 2 on the stability of hydrogen removal is much greater than that of adding an insulating carrier to the hydrogen removal catalyst.
[0068] From the comparison between Example 1 and Example 2, it can be seen that no matter whether the membrane electrode is prepared using 80 μm proton exchange membrane 4 or 127 μm proton exchange membrane 4, the effect of the insulating layer 2 on reducing the hydrogen content in oxygen and improving the hydrogen removal stability is equally obvious.
[0069] From the comparison between Example 1 and Example 3, it can be seen that no matter whether a short-chain branched PFSA or a long-chain branched PFSA is used, the effect of the insulating layer 2 on reducing the hydrogen content in oxygen and improving the hydrogen removal stability is equally obvious.
[0070] From the comparison between Example 1 and Example 4, it can be seen that no matter whether platinum black or palladium carbon is used as the dehydrogenation catalyst, the effect of the insulating layer 2 on reducing the hydrogen content in oxygen and improving the dehydrogenation stability is equally obvious.
[0071] It should be noted that the specific parameters or some reagents in the above embodiments are specific embodiments or preferred embodiments of the present invention, rather than limiting the present invention; those skilled in the art can make adaptive adjustments within the scope of the present invention.
Claims
1. A low hydrogen permeability PEM water electrolysis membrane electrode, characterized in that: The PEM water electrolysis membrane electrode comprises, from top to bottom, an anode catalyst layer, an insulating layer, a hydrogen removal layer, a proton exchange membrane and a cathode catalyst layer, wherein the raw material for preparing the insulating layer comprises perfluorosulfonic acid resin.
2. The low hydrogen permeability PEM water electrolysis membrane electrode according to claim 1, characterized in that: The method for preparing the insulating layer comprises the steps of: Dispersing perfluorosulfonic acid resin in an alcohol aqueous solution to obtain an insulating layer slurry; The insulating layer slurry is coated on the surface of the base film using a coating machine, and then heated and dried to obtain the insulating layer.
3. The low hydrogen permeability PEM water electrolysis membrane electrode according to claim 2, characterized in that: The bottom plate temperature of the coating machine is 25℃~30℃, the coating wet film thickness is 50μm~120μm, the coating rod line speed is 0.1 m / min~0.5m / min, the heating and drying time is 1 min~15min, and the insulation layer thickness is 5μm~15μm.
4. The low hydrogen permeability PEM water electrolysis membrane electrode according to claim 2, characterized in that: The alcohol includes at least one of methanol, ethanol, n-propanol, isopropanol, ethylene glycol, n-butanol, isobutanol and sec-butanol.
5. The low hydrogen permeability PEM water electrolysis membrane electrode according to claim 1, characterized in that: The steps of preparing the hydrogen removal layer include: The hydrogen removal layer slurry is coated on the surface of the base film, heated and dried to obtain the hydrogen removal layer.
6. The low hydrogen permeability PEM water electrolysis membrane electrode according to claim 5, characterized in that: The coating machine bottom plate temperature is 25~60℃, the coating wet film thickness is 50~120μm, the coating rod line speed is 0.1~0.5m / min, the drying time is 1~15min, the thickness of the dehydrogenation layer is 5~15μm, and the dehydrogenation layer slurry contains platinum-palladium catalyst.
7. The low hydrogen permeability PEM water electrolysis membrane electrode according to claim 6, characterized in that: Platinum or palladium loading is 0.05~0.5 mg / cm 2 .
8. A method for preparing a low hydrogen permeability PEM water electrolysis membrane electrode according to any one of claims 1 to 7, characterized in that: Includes steps: The anode catalyst layer, the insulating layer, the hydrogen removal layer, the proton exchange membrane and the cathode catalyst layer are stacked together in sequence by transfer printing to obtain a low-hydrogen permeability PEM water electrolysis membrane electrode.
9. The preparation method according to claim 8, characterized in that: The transfer temperature is 80℃~180℃, the pressure is 2MPa~5MPa, and the transfer time is 2 min~10min.
10. The preparation method according to claim 8, characterized in that: The transfer includes the first transfer, the second transfer and the third transfer, and the specific steps are as follows: Placing the hydrogen removal layer and the proton exchange membrane in a transfer machine, and performing a first transfer printing to obtain a first transfer membrane; Placing the insulating layer and the first transfer film in a transfer machine for transfer printing, and performing a second transfer printing to obtain a second transfer film; The anode catalyst layer, the second transfer membrane and the cathode catalyst layer are placed in a transfer machine for transfer in sequence. After the third transfer, a low-permeability hydrogen PEM water electrolysis membrane electrode is obtained.
Citation Information
Cited By
Preparation method of deoxygenized hydrogen composite diffusion layer and composite diffusion layer
CN120666358A